"Revenue Management" Effects Related to Financial Flows Generated by Climate Policy - Strand, Jon (Washington, DC: World Bank, 2012)
This paper discusses possible macroeconomic implications for low-income countries of increased revenue inflows that may follow from implementing certain global greenhouse gas mitigation policies. Such revenue sources include revenue from emissions offset mechanisms, direct investments, and financial transfers that form parts of possible future mitigation treaties. In the short run such revenue will come mainly from offset markets and donor-sponsored programs, with some additional financial inflows due to foreign direct investments. In the longer run, comprehensive global cap-and-trade or carbon tax schemes could provide a potentially much larger revenue flow to many low-income countries. The author argues that the macroeconomic implications of such flows are manageable in the short run, but the larger revenues resulting from global emissions schemes could overwhelm this capacity and lead to a number of potential macroeconomic management problems.